Yajnakund outside the main temple - Temples of India Project Team (Jio Institute, 2024)
Southeast view of the mulaprasada (main temple). Comprising a mandapa (hall), antarala (vestibule or antechamber), and a garbhagriha (sanctum sanctorum) on its plan, the temple has a simple elevation with minimal decoration. Outside the main temple, there is a yajnakund for performing yajna and havan (fire rituals).